Association between quality of prenatal care and low weight at birth in a hospital institution in Feira de Santana/BA - Julita Maria Freitas Coelho; Caroline Ramalho Galvão; Raiza Melo Rodrigues; Silas Santos Carvalho; Bruna Matos Santos; Samilly Silva Miranda; Caroline Santos Silva; Edla carvalho Lima Porto; Lorena Ramalho Galvão (Universidade de Santa Cruz do Sul, 2018)
Background and Objectives: The greater adherence to prenatal care is directly related to the reduction of low birth weight (LBW), and the low frequency of the first is one of the major causes of the second. Thus, this study aimed to measure the association between prenatal quality (QPN) and BPN in users of a hospital in Feira de Santana/BA. Methods: A case-control study was carried out with 144 women admitted to the maternity ward for delivery. For the collection of data, the pregnant woman's card, the hospital chart and the application of questionnaires were used. Odds ratio (OR) were obtained for comparison of groups and multivariate analysis was performed to estimate the effect of PNQ on BPN. Results: A prevalence of 18.8% of newborns